Influence of Project Management Functions on Effective Implementation of Donor Funded Projects in Kenya - Kamba, Mwangangi Stephen; Mburu, Dr. David Kiarie (IJRDO - Journal of Applied Management Science, 2016)
Projects remain the instruments of choice for policy makers in international development.Yet, paradoxically, the poor implementation of projects and the disappointment of projectstakeholders and beneficiaries seem to have become the rule and not the exception incontemporary reality. Kenya is one of the countries that receive a lot of donor support toset up projects for the purpose of improving the status of its population such asemployment, alleviation of poverty, increase of economic performance and supportingsocial cohesion. Despite enormous resources channeled by donors in setting up theseprojects, little impact has been realized as trends in implementation rates continues tosurge as a result of lack of Project Management Functions. The main purpose of thisstudy was to establish influence of Project Management Functions on effectiveimplementation of donor funded projects in Kenya. The study was guided by thefollowing specific objectives: To find out the influence of planning and organizing oneffective implementation of donor funded projects in Kenya; To investigate the influenceof monitoring and evaluation on effective implementation of donor funded projects inKenya; To examine the influence of directing and controlling on effective implementationof donor funded projects in Kenya; To study the influence of directing and controlling oneffective implementation of donor funded projects in Kenya and to establish the influenceof coordination on effective implementation of donor funded projects in Kenya. The studywas built on the contingency theory, theory of constraints, theory of agency and theory ofchange. The target population of this study was 177 that is project managers (top andmiddle level), chairpersons of the beneficiary groups and representatives of the donoragencies in Mutitu Sub-County. Donor agencies and targeted beneficiaries from eachsampled donor funded projects. The primary data was gathered from the questionnaires